Mobile PEAR transcription factors integrate positional cues to prime cambial growth - Miyashima, Shunsuke; Wallner, Eva-Sophie; Greb, Thomas (Nature, 2019)
Radial growth in the roots of Arabidopsis, which is mediated by gene expression activated by the mobile PEAR1 and PEAR2 transcription factors, is initiated around protophloem-sieve-element cell files of procambial tissue.